KONSELING PASTORAL SEBAGAI PENDEKATAN HOLISTIK BAGI PENDERITA PENYAKIT GULA - Brayen Tinihada; Rifo Sendiang; Janhard Katampuge (PT. Giat Konseling Nusantara, 2026)
Diabetes mellitus is a chronic disease that not only affects patients physically, but also influences their psychological, social, and spiritual dimensions. Conventional medical approaches often fail to address the holistic needs of patients comprehensively. This article aims to examine the role of pastoral counseling as a holistic approach in accompanying people with diabetes mellitus. The method used is a literature study by analyzing various relevant scientific sources. The results show that pastoral counseling is able to provide significant emotional, spiritual, and social support for diabetic patients, complementing existing medical services. This approach has proven effective in improving patients’ quality of life by strengthening the dimension of faith, restoring self-esteem, and developing psychological resilience. The conclusion of this article affirms that the integration of pastoral counseling into holistic health services is essential to ensure the fulfillment of the total needs of human beings as bio-psycho-socio-spiritual creatures.